Purification of high-complexity peptide microarrays by spatially resolved array transfer to gold-coated membranes - Schirwitz, Christopher; Löffler, Felix; Felgenhauer, Thomas; Stadler, Volker; Nesterov-Müller, Alexander; Dahint, Reiner; Breitling, Frank; Bischoff, F. Ralf (Advanced materials, 2013)
A method for the one-step purification of high-complexity peptide microarrays is presented. The entire peptide library is transferred from the synthesis support to a gold coated polyvinylidenfluoride (PVDF) membrane, whereby only full-length peptides covalently couple to the receptor membrane via an N-terminally added cysteine. Highly resolved peptide transfer and purification of up to 10 000 features per cm2 is demonstrated.